Atenção à saúde da mulher: proposta de roteiro de consulta - BORGES, Ana Paula Anunciação (2019)
The Program for Integral Attention to Women's Health is designed to provide comprehensive care, their guidelines were developed within the perspective of primary health care and encompass all phases of life, from adolescence to old age. Thus, we aimed to carry out a survey of major existing protocols and used in PAISM in Brazilian municipalities and develop a roadmap for consultation on women attention básica.Trata is a Literature Review (RL), which earned the analysis of relevant research on the theme 'protocols attention to women's health', published between the years 2003-2013. Based on the characteristics of the protocols found in the RL was created a unique instrument to be used in the care of women in primary care network health. It was possible to conduct a survey of the main difficulties encountered by health professionals to consult with women, the main causes for this woman to seek health care and how it is working PAISM in Brazil. The protocol made by this study was structured to, along with other available resources, optimizing care. Should not become a questionnaire to be filled so unchanging, freezing assistance in the simple act of filling a placard. It is important that the multidisciplinary team is able to use the same, so that remains a feature of the service in a way that fully encompasses each user.